Acetylation of PGK1 promotes liver cancer cell proliferation and tumorigenesis. Issue 2 (29th November 2016) - Hu, Hongli; Zhu, Wenwei; Qin, Jun; Chen, Min; Gong, Liyan; Li, Long; Liu, Xiangyuan; Tao, Yongzhen; Yin, Huiyong; Zhou, Hu; Zhou, Lisha; Ye, Dan; et al.
Abstract : Phosphoglycerate kinase 1 (PGK1) is an important enzyme in the metabolic glycolysis pathway. In this study, we observed a significant overexpression of PGK1 in liver cancer tissues and a negative correlation between PGK1 expression and liver cancer patient survival. Furthermore, depletion of PGK1 dramatically reduced cancer cell proliferation and tumorigenesis, indicating an oncogenic role of PGK1 in liver cancer progression. Moreover, we identified acetylation at the K323 site of PGK1 as an important regulatory mechanism for promoting its enzymatic activity and cancer cell metabolism. And we further characterized P300/cyclic adenosine monophosphate response element binding protein–binding protein–associated factor (PCAF) and Sirtuin 7 as the enzymes regulating K323 acetylation from both directions in liver cancer cells. Conclusion : These findings demonstrate a novel regulation of PGK1 as well as its important role in liver cancer progression. (Hepatology 2017;65:515‐528).